2011
DOI: 10.1021/jf200216r
|View full text |Cite
|
Sign up to set email alerts
|

Cooking Process: A New Source of Unintentionally Produced Dioxins?

Abstract: To improve understanding of human background exposure to dioxins, the influence of cooking on dioxin concentrations in food has received much attention. Studies have focused on changes in the distribution of dioxins that originate from raw foods. However, the possibility of dioxin formation during cooking has been neglected. In this study, cooking experiments were designed to investigate the generation of dioxins during cooking at high temperature and with flavorings containing organic chlorine. Solid, liquid,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 17 publications
3
18
0
Order By: Relevance
“…Also, no appreciable differences in PAH loads were observed in the oil before and after heating (Purcaro et al, 2006). The formation and distribution of PCNs is in accordance with previous observations that de novo produced dl-PCBs and PCDD/Fs were mainly present in the cooking oil fumes Wu et al, 2011).…”
Section: Effects Of Chlorine-containing Compounds and Temperature On supporting
confidence: 90%
See 1 more Smart Citation
“…Also, no appreciable differences in PAH loads were observed in the oil before and after heating (Purcaro et al, 2006). The formation and distribution of PCNs is in accordance with previous observations that de novo produced dl-PCBs and PCDD/Fs were mainly present in the cooking oil fumes Wu et al, 2011).…”
Section: Effects Of Chlorine-containing Compounds and Temperature On supporting
confidence: 90%
“…CN 66/67 and CN 73 were the dominant congeners and accounted for approximately 70% of the total TEQs of the PCNs. The congener patterns of the dl-PCBs and PCDD/Fs in the oil fumes were similar to those previously reported, and will therefore be discussed no further in the current paper Wu et al, 2011).…”
Section: Comparison Of Dl-pcns Dl-pcbs and Pcdd/fssupporting
confidence: 84%
“…Moreover, other methods, including market basket study, and monitoring program, were also applied to evaluate the dietary intake for residents in many countries (Arisawa et al, 2008;Perelló et al, 2010;Marin et al, 2011;Törnkvist et al, 2011;Rauscher-Gabernig et al, 2013;Husain et al, 2014). Some studies have indicated that cooking process might be a source of PCDD/Fs and dl-PCBs Wu et al, 2011). The calculation of dietary intake from cooked foods could therefore lead to a more accurate evaluation.…”
Section: Dietary Intake Estimationmentioning
confidence: 99%
“…Briefly, the samples were spiked with 1 ng of a 13 C 12 -labeled PCDD/Fs internal standard (Wellington Laboratories) (Wu et al 2011) before accelerated solvent extraction (hexane/dichloromethane = 1:1). The extract was then sequentially cleaned using a multilayer silica gel and basic alumina columns.…”
Section: Soil Samplingmentioning
confidence: 99%